Provincial Political Power and the Political Press: Between Press Freedom and Opinion Control (Entre Ríos, 1862-1870) (Quinto Sol, 2018)
This paper analyzes the press control practices used by the provincial political powers of Entre Ríos between 1862 and 1870. This period was characterized by an increasing political dispute and the deepening of public debate. An indication of this process is the increase in the number of newspapers and the diversity of their political positions. Most of the newspapers were Federalists and supporters of Urquiza, but they maintained a space of discursive autonomy and what was published did not always go along the lines of the caudillo´s interest. Also, there were Unitary and dissident Federal newspapers which were very critical of the provincial government and the figure of Urquiza. Respect for press freedom as a legitimating principle of the exercise of power prevented the development of legislation restricting that freedom and discouraged the practice of filing law suits for libel against publishers or journalist among provincial officials. Hence, the way in which political power managed to limit opinion was dominated by informal practices of political control.
Keywords: Press; politics; 19th century; Argentina; Entre Ríos